Isi Buku Pegangan Perkuliahan Teori Belajar dan Upaya Memahaminya dalam Proses Pembelajaran di Program S1 Teknologi Pendidikan - Suharjo Dwijosumarto (Universitas Negeri Malang, 2016)
This research was aimed at analysing the content of reference books used in theories of learning courses and the efforts to understand them. This research was held in the Department of Educational Technology, State University of Surabaya. The data were gathered by using questionnaires, documentations, and observations, and were then analysed by descriptive statistics. The result showed that the references were relevant to theories of learning subject, the students did not find difficulties in studying the references, and that the references helped the students in writing papers and achieving better outcomes